Folliculitis Decalvans and Lichen Planopilaris Phenotypic Spectrum: A Case Report - Zhang X; Zhu M; Zhou J; Wu S; Liu J; Qin Q (Clinical, Cosmetic and Investigational Dermatology, 2022)
Xi Zhang, Mingfang Zhu, Jia Zhou, Shuhui Wu, Juan Liu, Qiuyan Qin Department of Dermatology, The Second Affiliated Hospital of Hunan University of Chinese Medicine, Changsha, People’s Republic of ChinaCorrespondence: Mingfang Zhu, Department of Dermatology, The Second Affiliated Hospital of Hunan University of Chinese Medicine, 233 Cai E North Road, Kaifu District, Changsha, People’s Republic of China, Tel +86-13907317358, Fax +86-0731-84917727, Email 20153203@stu.hnucm.edu.cnAbstract: The folliculitis decalvans (FD) and lichen planopilaris (LPP) phenotypic spectrum combines biphasic features of FD and LPP. It is characterized by successive or concomitant occurrence of pustules, crusts, follicular tufts, perifollicular erythema, perifollicular scales, and cicatricial alopecia and includes mixed histologic features of both FD and LPP. Here, we report the case of a 33-year-old female patient with a 30-year history of FD-LPP phenotypic spectrum lesions.Keywords: primary cicatricial alopecia, biphasic features, pustules, perifollicular erythema, follicular tufts